Peningkatan Minat Terhadap Mata Kuliah Pendidikan Jasmani MelaluI Penggunaan Media Pembelajaran Berbasis Animasi Gift - Joni Muis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
The purpose of this research is to improve the physical education learning interest and analyze the response of students during the learning process using animation-based media gift. The products of this research are 1) report on the use of media-based learning animation and problem solving theory, research subjects students UPP Parepare third semester of the academic year 2016/2017 Prodi PGSD FIP UNM totaling 25 people. The procedure of this study include 1) the manufacture of lattice questionnaire interest in learning, 2) preparation of data collection equipment, 3) triangulation and verification of data, 4) data collection, data analysis and processing. Based on the results and discussion, it was concluded that the use of an animated picture media can increase student interest in understanding the material of PE, the results of the questionnaire statement showed 85.71% or higher qualification.